Essays on the history of moral philosophy - Schneewind, J. B. (Jerome B.), 1930- (Oxford : Oxford University Press, 2010)
J.B. Schneewind presents a selection of his published essays on ethics, the history of ethics and moral psychology, together with a new piece offering an intellectual autobiography. The essays range across the 17th, 18th, and 19th centuries, with a particular focus on Kant and his relations to earlier thinkers.
Description based on print version record.
Includes bibliographical references.
Keywords: Ethics -- History; Ethics